Selenium supplementation during fermentation with sugar beet molasses and Saccharomyces cerevisiae to increase bioethanol production - Faramarzi Sara (Green Processing and Synthesis, 2019)
A bench scale submerged fermentation process was used to bioethanol produce using sugar beet molasses and Saccharomyces cerevisiae, as substrate and microbial strain, respectively. Effects of selenium amount on growth of S. cerevisiae and bioethanol production were evaluated. The obtained results indicated that growth of S. cerevisiae (manifested as turbidity intensity) in the samples containing 0, 5, 10, 15, 20 and 25 μg sodium selenite, during aerobic process, was 0.1707, 0.1678, 0.1679, 0.1664, 0.1627 and 0.160% a.u./h (after 14 h incubation), respectively. Statistical analysis based on compression test indicated that there were insignificant (p > 0.05) differences between growth rate of the yeast in the fermented samples containing S. cerevisiae and 5 to 25 μg selenium salt. Response surface methodology was utilized to evaluate effects of two fermentation parameters namely, amount of selenium (5-25 μg) and substrate brix (10-25°Bx) on the concentration (g/L) of produced bioethanol. Obtained results revealed that maximum bioethanol concentration (55 g/L) was achieved using 15 μg selenium and molasses with 25°Bx. Furthermore, results have also indicated that, without using selenium and using molasses with 25°Bx, bioethanol with concentration of 29 g/L was produced.